Red-taping agricultural research - Jha, Dayanatha (2002)
The committee constituted to review the Indian Council of Agricultural Research has a serious credibility problem. it is a committee of bureaucrats and management experts with just one agricultural scientist. - Reproduced.
Keywords: Agricultural research